Peculiarities of morphological and functional restructuring of rat testicular parenchyma against the background of aortoiliac segment occlusion (experimental study) - Koval , D.V.; Levenets , O.O.; Chvankina , R.I.; Smachylo , I.V.; Mykolenko , A.Z. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. The most frequent factors leading to disorders of testicular hemodynamics include varicose veins of the vine plexus (10-35 %), the presence of an oblique inguinal hernia (1 %), or hernioplasty. Under these conditions, the structures of the spermatic cord are partially compressed, resulting in acute or chronic testicular ischemia, increased venous pressure, and disorders of thermoregulation. Objective. To determine the peculiarities and nature of the dynamics of the vascular bed restructuring of the testes of white rats in case of dosed stenosis of the aortoiliac segment. Methods. The experiment was performed on 48 white outbred mature male rats. The experimental group consisted of 36 animals with modeled dosed stenosis of the aortoiliac segment. On days 1, 3, 7, and 14, the animals were withdrawn from the experiment and evaluated. Results. One day after the creation of experimental stenosis of the aortoiliac segment, a significant edema of the organ stroma was detected during microscopic examination of the testicular structures. On the third day of observation, the previously detected signs of organ circulatory disorders of the testis continued to increase. The swelling of the testicular interstitial tissue decreased slightly, but it was accompanied by changes in the structure of spermatogenic epithelial cells. On day 7 of the experiment, with a marked decrease in edema between the loops of the seminiferous tubules, dystrophic changes in the testicular tissue began to be detected. In particular, the arteries of larger caliber were stretched due to significant blood filling. On the 14th day of observation, signs of organ hemodynamics disorders were detected, which led to disorders of testicular tropism in experimental animals. The manifestation of such changes was a pronounced arterial and venous hemorrhage. Conclusion. The results of the histological study indicate that experimental stenosis of the aortoiliac segment leads to significant circulatory disorders in the testes of male rats.